Relations Between Dual Filial Piety and Life Satisfaction: The Mediating Roles of Individuating Autonomy and Relating Autonomy - Sun, Peizhen; Fan, Xiaoyue; Sun, Yudi; Jiang, Hongyan; Wang, Lu (Frontiers in Psychology, 2019)
Filial piety (FP) was formerly a Confucian concept that specifies how children should treat their elders. In recent years, some psychologists have postulated that there are considerable overlaps between Chinese FP and notions found in other cultures. They have redefined FP as a contextualized personality emphasizing the psychological schema of parent-child interaction so that it fits universal cultural contexts. Based on this theory construction, this study aimed to examine the effects of reciprocal FP and authoritarian FP on life satisfaction and the mediating roles of individuating autonomy and relating autonomy therein. To do so, we recruited and surveyed 360 high school students in China. Subsequently, a mediation model based on the Dual Filial Piety Model and previous studies was tested. Results demonstrate that reciprocal FP predicted life satisfaction positively and that both individuating autonomy and relating autonomy played significant mediating roles in the relationship between reciprocal FP and life satisfaction. Moreover, authoritarian FP had a negative indirect effect on satisfaction through the mediating role of individuating autonomy, while authoritarian FP had a positive indirect influence on satisfaction through the mediating role of relating autonomy. The theoretical and practical implications of these findings are discussed.